Pemetaan Sebaran Keanekaragaman Jenis Tanaman Hias Desa Petiga, Kecamatan Marga, Kabupaten Tabanan - Vidyaswari, Ni Made Ayu Regita; Semarajaya, Cokorda Gede Alit; Mayadewi, Ni Nyoman Ari (Jurnal Arsitektur Lansekap, 2023)
Mapping of the Distribution of Ornamental Plants Species Diversity in Petiga Village, Marga District, Tabanan Regency. Petiga Village has been one of the well-known destinations of ornamental plants in Bali for about 30 years. Most of the people here work as farmers. The land of the local community's house is used as a nursery and business activities for plant farming. The purpose of this research was to inventory and map the distribution of ornamental plant species diversity in Petiga Village, Marga District, Tabanan Regency. The method used in this research was the survey method with data collection techniques through observation, interviews, and literature study. The results of the data analysis were tabulated, mapped, and presented in the form of a map of the distribution of ornamental plants in Petiga Village. The results showed a total of 142 types of ornamental plants species that can be found in Petiga Village. A picture of the landscape phenomenon in Petiga Village includes things such as the number of species, farmers' income, and the selling price of ornamental plants and also the number of mother plants. Maintaining and empowering ornamental plant farmer groups is still lacking, so the community needs to form an organization of ornamental plant farmers to preserve the village landscape so that it is more orderly and sustainable in the future.